Study on antioxidant activity of certain plants in Thailand: Mechanism of antioxidant action of guava leaf extract - Tachakittirungrod, Suganya; Okonogi, Siriporn; Chowwanapoonpohn, Sombat (Food chemistry, 2007)
The ethanol extracts from 24 samples plant species commonly found in Thailand were investigated and compared on their antioxidant activity by ABTS assay. The ethanol extract from the leaves of guava ( Psidium guajava) showed the highest antioxidant capacity with the TEAC value of 4.908 ± 0.050 mM/mg, followed by the fruit peels of rambutan ( Nephelium lappaceum) and mangosteen ( Garcinia mangostana) with the TEAC values of 3.074 ± 0.003 and 3.001 ± 0.016 mM/mg, respectively. The further investigation of guava leaf extracts from different solvents; n-hexane, ethyl acetate, n-butanol, and methanol, was examined using ABTS and FRAP assays. The total phenolic content was done by Folin–Ciocalteu reaction. The results indicated that the methanol fraction possessed the highest antioxidant activity, followed by the butanol and ethyl acetate fractions, respectively. The hexane fraction showed the lowest antioxidant activity. The results demonstrated that the mechanism of antioxidant action of guava leaf extracts was free radical scavenging and reducing of oxidized intermediates. The phenolic content in guava leaf fraction played a significant role on the antioxidant activity via reducing mechanisms.